STUDI KOMPARATIF PENDAPATAN USAHA MEUBEL SEBELUM DAN SETELAH PANDEMI COVID-19 - Patra, I Ketut; Sukma, Anita; Bustami, Lanteng; Hapid, Hapid (Universitas Gajah Putih, 2022)
ABSTRACT This study aims to determine a comparative study of furniture business income before and after the covid-19 pandemic in Palopo City. The subject of this research is furniture in Palopo City. The population in this study was all furniture in Palopo City, the sample in this study was 11 furniture. This research was conducted in Palopo City. This research uses a case study method or approach. This type of research is descriptive quantitative by taking primary and secondary data related to furniture business income before and after the covid-19 pandemic at the research site. Data collection techniques include observation, interviews, and documentation. The results showed that most of the furniture business income before and after the covid-19 pandemic in Palopo City experienced a decline in income during this covid-19 pandemic. Keywords: Covid-19 Pandemic, Impact of Covid-19 Pandemic, Furniture Business Income